“Path Dependence” in the Socio-Cultural Context of Armenian Institutional Development - Gharagulyan, Arman (Bulletin of Yerevan University E: Philosophy, Psychology, 2026)
The collapse of the Soviet Union triggered an unprecedented wave of institutional transformations across the post-Soviet space, predicated on the assumption that liberal-democratic frameworks would automatically catalyze socio-cultural modernization. However, the decades-long "transition" has revealed a profound structural asymmetry: while formal institutions were successfully adopted, the "cultural codes" and social memory underlying public life remained tethered to a paternalistic past. Armenia provides a stark illustration of this phenomenon, where persistent path dependence has induced a state of institutional "lock-in," often rendering democratic reforms merely decorative.The article argues that transcending this developmental inertia necessitates a radical form of institutional engineering targeting the society's existential foundations. In this framework, the "Real Armenia" concept is analyzed as an attempt to deconstruct traumatic memory and pragmatically reconfigure national identity. Concurrently, the study identifies the challenges that leave this concept existentially vulnerable. The author posits that the erosion of traditional pillars of ontological security and the resulting responsibility overload can provoke public resistance and a retreat into passive paternalism. The conclusion suggests that overcoming "path dependence" is most viable by converting historical traumas into state-building resources and fostering a civic agency where the state is perceived as the definitive environment for individual security and self-actualization.
Keywords: path dependence; post-Soviet transformation; cultural code; Real Armenia; learned helplessness; institutional engineering